(untitled) (Asian Journal of Pharmaceutics (AJP), 2020)
Aim: The present research is aimed to develop and evaluate sonidegib loaded poly(ethyl methacrylate) nanoparticles (PEM-NPs) to improve its resistance toward pH and chemical conditions in exposed cancerous lesions. Materials and Methods: The polymer PEM is prepared from ethyl methacrylate (monomer) followed by designing 17 formulations of sonidegib loaded PEM-NPs using 3-factor, 3-level Box–Behnken design, and the results analyzed using Stat-Ease Design Expert® software V8.0.1. Three optimal batches (F1, F2, and F3) with comparable values of observed and predicted values are characterized for particle size, polydispersity index (PDI), zeta potential (ZP), entrapment efficiency, and percentage drug loading. The formulation (F3) with minimum particle size and maximum percentage conversion is further subjected to powder X-ray diffraction (PXRD), Fourier-transform infrared (FTIR), scanning electron microscopy (SEM) studies, drug release, and stability study. Results and Discussion: The particle size of sonidegib PEM-NPs (F1, F2, and F3) ranges between 191.5 ± 42.9 nm to 355 ± 39.7 nm and PDI 0.454 to 0.626. The ZPs are within the acceptable limits of −22.9 ± 2.48 mV–−24.7 ± 1.89 mV. The entrapment efficiency of the NPs ranges between 68.46 ± 0.37% and 70.24 ± 0.18% and percent drug loading between 20.62 ± 2.12% and 21.24 ± 1.72. The in vitro release study indicated an improvement in drug release of formulation F3 (95.878%) in comparison with the pure drug (2.86%). The optimized formulation F3 characterized for FTIR, PXRD, and SEM studies indicated molecular state dispersion of the drug with the polymers. The stability studies conducted for 90 days indicated that the developed formulation is stable. Conclusion: Sonidegib loaded PEM-NPs prepared using 3-factor, 3-level Box–Behnken design with increased solubility and stability.